Beyond the Bright Side: Dark Personality at Work. Issue 1 (January 2015) - Harms, P.D.; Spain, Seth M.
<x xml:space="preserve">Abstract</x> Despite the long history of the psychological study of dark personality characteristics and the recent surge of interest in the topic, much work remains to fully understand the breadth and depth of the impact of dark personality in the workplace. This commentary briefly covers the history of dark personality, discusses the place of this special issue within that history, and then proposes a number of avenues for future research in terms of defining, measuring, and providing a more comprehensive theoretical framework for the study of dark personality.